Optimalisasi Penerapan Fungsi Pelaksanaan (Actuating) dalam Meningkatkan Kinerja Kegiatan Siswa di SMK Makarya 1 Jakarta - Ulung Nur Wahit; Guntur Maulana; Khuzaima Az Zahra; Ahmad Nurhadi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The implementation function (actuating) plays an important role in ensuring that organizational activities are carried out effectively and in accordance with predetermined objectives. However, student activities in schools often encounter challenges related to communication, coordination, participation, and task implementation, which may reduce the effectiveness of organizational programs. This community service activity was conducted at SMK Makarya 1 Jakarta to enhance students' understanding of the implementation function and encourage better performance in school organizational activities. The program was delivered through interactive presentations, discussions, question-and-answer sessions, and ice-breaking activities to promote active participation. Throughout the activity, students were introduced to the importance of leadership, motivation, teamwork, communication, and responsibility in supporting successful organizational implementation. The activity was well received, as reflected in the students' enthusiasm during discussions and their ability to explain the application of the implementation function in school activities. In addition, participants demonstrated a better understanding of the importance of collaboration and effective communication in achieving organizational goals. This community service program is expected to encourage students to apply management principles in daily school activities and contribute to the development of more organized, active, and productive student organizations.